Molecular identification of the trematode Paragonimus in faecal samples from the wild cat Prionailurus bengalensis in the Da Krong Nature Reserve, Vietnam. Issue 6 (21st September 2015) - Doanh, P.N.; Hien, H.V.; Tu, L.A.; Nonaka, N.; Horii, Y.; Nawa, Y.
Abstract: Conventional identification of Paragonimus species and their natural definitive hosts is based on the morphological features of adult parasites isolated from the lungs of wild mammalian hosts. However, wild animals are protected by strict regulations and sampling is not always possible. Recently, molecular techniques have been developed to identify the internal transcribed spacer (ITS) sequences of Paragonimus eggs in faeces/sputum of human patients. Also, mammalian hosts can be identified using the D-loop sequence of mitochondrial DNA in faecal samples. In this study, we used molecular techniques on faeces from wild animals collected in Da Krong Nature Reserve, Quang Tri province, central Vietnam, where Paragonimus metacercariae are highly prevalent in mountain crabs, to identify Paragonimus species and their natural definitive hosts. The results indicated that wild cats, Prionailurus bengalensis, were infected with at least three different Paragonimus species, P. westermani, P. skrjabini and P. heterotremus . Because all of these species can infect humans in Asian countries, human paragonimiasis should be considered in this area.